Management of acute pulmonary embolism with sequential hybrid therapy of surgical thrombectomy and rivaroxaban intensive therapy: a case report. Issue 4 (20th April 2023) - Migita, Shohei; Murata, Nobuhiro; Fukamachi, Daisuke; Fukumoto, Katsunori; Arai, Riku; Uchiyama, Hiroe; Tago, Kenichiro; Okada, Masahiro; Tanaka, Masashi; Okumura, Yasuo
Abstract: Acute pulmonary embolism (PE) is often associated with rapid hemodynamic deterioration or death. Therefore, early therapeutic intervention is important. A 45-year-old man was diagnosed with intermediate-high risk PE, and sequential hybrid therapy consisting of surgical thrombectomy and rivaroxaban intensive therapy was administered. During the course of treatment, echocardiography revealed improvement in pulmonary artery systolic pressure, and thrombus volume analysis by computed tomography revealed a drastic reduction in the size of the thrombus. Sequential hybrid therapy for acute PE not only stabilizes hemodynamics, but may also prevent conversion to chronic thromboembolic pulmonary hypertension by sufficiently reducing the volume of the thrombus.